2010
DOI: 10.1039/c0cp00417k
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of liquid imidazole using a high-rank quantum topological electrostatic potential

Abstract: Rigid body molecular dynamics simulations were carried out on pure liquid imidazole at four different temperatures and at 1 atm. Imidazole, which is important both in life science and materials science, is one of the simplest molecules to possess both a lone pair and a π system. These two features are known to benefit from multipolar electrostatics. Here the electrostatic interaction is governed by atomic multipole moments obtained from topologically partitioned ab initio electron densities. The non-electrosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 67 publications
4
39
0
Order By: Relevance
“…These peak distances are shorter than the r NN peak of 2.9 Å found in liquid imidazole, 47 indicating the stronger HB between imH + and imidazole than that between the imidazole molecules. The stronger HB associated with imH + can also be found by comparing Figure 3 2.69 Å, respectively, with B3LYP/6-311G** level of theory.…”
Section: Iii1 the Solvation Of The Proton In Imidazolementioning
confidence: 67%
See 1 more Smart Citation
“…These peak distances are shorter than the r NN peak of 2.9 Å found in liquid imidazole, 47 indicating the stronger HB between imH + and imidazole than that between the imidazole molecules. The stronger HB associated with imH + can also be found by comparing Figure 3 2.69 Å, respectively, with B3LYP/6-311G** level of theory.…”
Section: Iii1 the Solvation Of The Proton In Imidazolementioning
confidence: 67%
“…Comparing to the NHB-NNB RDF in liquid imidazole,47 in which the first peak appears at ~ 2.9 Å, it can be seen that the effect of the excess proton does not extend beyond the first solvation shell, highlighting the spatial localization feature of PT in imidazole. On the other hand, when the first peak of g(r NN ) represents the imidazoles between the first and the second solvation shell of imH + , as shown inFigure 6(e) and 6(f), it peaks at ~3.0 Å.…”
mentioning
confidence: 96%
“…However, molecular dynamics (MD) simulations illustrated that chain-like hydrogen-bonding is more likely than such stacked structures, both in aqueous solutions at different concentrations 46 and in liquid imidazole. 47 MD simulations also indicated that the local structure around the imidazole molecules does not change strongly as a function of concentration. 46 A recent NEXAFS study of imidazole solutions 17 supported the MD simulation results, in that the N K-edge absorption spectra exhibited only minor changes in the concentration range from 0.5 to 8.2 M. The XRS study reported here complements this NEXAFS study 17 and extends the scope of characterization to the supersaturated state.…”
Section: Introductionmentioning
confidence: 93%
“…Our spectroscopic results thus supply important energy sequence benchmarks for the testing and improvement of intermolecular imidazole and histidine force fields. 27 Imidazole-water turns out to be a clear-cut case where direct absorption spectroscopy in a free jet provides thermodynamic control, whereas matrix and helium droplet isolation offer kinetic control, and phenyl substitution to enable UV/IR double resonance may lead to an incomplete picture.…”
mentioning
confidence: 99%